The Influence of the Make A Match Type Cooperative Learning Model on the Collaboration Ability and Learning Outcomes of Class V Students of UPT SPF SDN Mangkura I Makassar City - Yusriana, Yusriana; Yunus, Muh; Yahya, Muh; Yunus, Irham Maulana (CV. Rayyan Dwi Bharata, 2025)
The objectives of this research are as follows: (1) to explain the learning process for science subjects using the Make A Match type cooperative learning model for class V UPT SPF SDN Mangkura 1 students, (2) to show how to use the Make A Match type cooperative learning model in The science and science subject has an impact on the ability to work together in class V students of UPT SPF SDN Mangkura 1, and (3) shows how the use of the Make A Match type cooperative learning model in the science and science subject has an impact on this research. This research uses quantitative methods. The type of research used is experiments with original experimental designs and control-only experiments using experimental and control classes. In this research, the experimental sample was class V A students, and the control group was class V B students. Data collection techniques used observation, tests and documentation. Analysis of learning abilities, analysis of learning outcomes, and hypothesis testing are used to analyze the data that has been collected further (t test). The results of the research show that the make a match cooperative learning model can influence students' ability to learn to work together in class V science subjects at UPT SPF SDN Mangkura. This can be seen from students who are very involved in the problem solving and learning process. Learning outcomes in class V science subjects at UPT SPF SDN Mangkura can be influenced by the make a match cooperative learning model. This can be seen from the students' seriousness during the learning process by listening to the lesson material presented by the teacher, which helps students understand the material and improve their learning outcomes.